Asperger Syndrome and Employment : Adults Speak Out about Asperger Syndrome. - Edmonds, Genevieve (Adults Speak Out about Asperger Syndrome., 2008)
'This is the book we need for guidance on employment for people with Asperger's syndrome. The contributors describe their employment experiences and offer sound advice. I thoroughly enjoyed reading the success stories and took note of the words of warning of what not to do.'. - Professor Tony Attwood, author of The Complete Guide to Asperger's Syndrome. Employment is an important part of a healthy, balanced and fulfilling life but less than 20 per cent of people with Asperger Syndrome (AS) are in work at any one time. The adults with AS in this book explore the issues surrounding employment, p.